Application of density as a parameter in description of failure stress under uniaxial loading of softwood in LR orthotropy plane (Archives of Mechanics - Test, 2007)
A description of failure stress for tension and compression of pinewood in the LR orthotropy plane, in accordance with the Mises, Ashkenazi–Ganov and Tsai–Wu criteria, is presented in the work. The tests for pinewood has shown that strength depends on density along the L-direction. This dependence was used for the description of the pinewood failure stress. The choice of the criterion was determined by the possibility to describe correctly the failure stress, assuming that the failure stress function goes through the values of strength obtained from the tests in the L and R directions. An analysis of the above criteria leads to the choice of the Ashkenazi–Ganov criterion as the most precise criterion describing the experimental data.